Tailoring polyethersulfone/quaternary ammonium polysulfone ultrafiltration membrane with positive charge for dye and salt selective separation. Issue 18 (22nd May 2020) - Li, Jiaye; Cui, Zhenyu; Tao, Ran; Yang, Shuqian; Hu, Mengyang; Matindi, Christine; Gumbi, Nozipho N.; Ma, Xiaohua; Hu, Yunxia; Fang, Kuanjun; Li, Jianxin
Abstract: Polyethersulfone (PES)/quaternary ammonium polysulfone (QAPSf) blend ultrafiltration (UF) membranes with positive charge were fabricated by nonsolvent induced phase separation (NIPS) for use in dye and salt selective separation. QAPSf was synthesized by nucleophilic substitution with chloromethylated polysulfone (CMPSf). The effect of the PES/QAPSf mass ratio on the morphology and performance of blend UF membranes were studied. The membranes' zeta potentials gradually changed from negative to positive with decreases in the PES/QAPSf mass ratio. At PES/QAPSf mass ratios of 30:70 and 10:90, the zeta potentials of the membranes reached +1.8 mV and + 5.9 mV, respectively. Additionally, the contact angles of the membranes decreased from 74° to 52° as the QAPSf content increased from 0 wt% to 90 wt%. Furthermore, the membrane with a PES/QAPSf mass ratio of 30:70 showed a high water permeance (181.4 LMH bar −1 ) and excellent dye and salt selective separation performance. The rejection ratios reached 99.1%, 87.8%, 99.6%, and 92.4% for dyes Congo red, methyl blue, Alixin blue 8GX, and basic blue 24, respectively, while those for salts Na2 SO4, MgSO4, MgCl2, and NaCl were ≤ 10%. In addition, the PES/QAPSf membranes showed excellent antifouling performance and good operating stability with dye‐salt mixtures of various pHs and salt concentrations. Abstract : Polyethersulfone (PES)/quaternary ammonium polysulfone (QAPSf) blend ultrafiltration (UF) membranes with positive charges were fabricated using nonsolvent‐induced phase separation (NIPS) for dye and salt selective separations. PES and QAPSf blend system was completely compatible, and the membrane surface potential was tailored from negative to positive charges. The blend membrane exhibits outstanding dye/salt selective separation performance. In addition, the PES/QAPSf membranes show good antifouling performance and operating stability for dye‐salt mixtures.